Clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR‐associated genome‐editing toolkit to enhance salt stress tolerance in rice and wheat. Issue 2 (4th March 2022) - Nazir, Romaan; Mandal, Sayanti; Mitra, Sicon; Ghorai, Mimosa; Das, Neela; Jha, Niraj Kumar; Majumder, Madhumita; Pandey, Devendra Kumar; Dey, Abhijit
Abstract: The rice and wheat agricultural system is the primary source of food for billions across the world. However, the productivity and long‐term sustainability of rice and wheat are threatened by a large number of abiotic stresses, especially salinity stress. Salinity has a significant impact on plant development and productivity and is one of the leading causes of crop yield losses in agricultural soils worldwide. Over the last few decades, several attempts have been undertaken to enhance salinity stress tolerance, most of which have relied on traditional or molecular breeding approaches. These approaches have so far been insufficient in addressing the issues of abiotic stress. However, due to the availability of genome sequences for cereal crops like rice and wheat and the development of genome editing techniques like clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR‐associated protein9 (Cas9), it is now possible to "edit" genes and influence key traits. Here, we review the application of the CRISPR/Cas9 system in both rice ( Oryza sativa L.) and wheat ( Triticum aestivum L.) to develop salinity tolerant cultivars. The CRISPR/Cas genome editing toolkit holds great promise of producing cereal crops tolerant to salt stress to increase agriculture resilience with a strong impact on the environment and public health.